2019
DOI: 10.1371/journal.pone.0210170
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the delay with different anticoagulants before elective electrical cardioversion for atrial fibrillation/flutter

Abstract: AimsTo assess the impact of the introduction of direct oral anticoagulants upon the outcomes from elective electrical cardioversion for atrial fibrillation.MethodsThis is a retrospective comparison of delay to elective cardioversion with different anticoagulants. The data was gathered from a large regional hospital from January 2013 to September 2017. There were 3 measured outcomes: 1) the time in weeks from referral to the date of attempted electrical cardioversion; 2) the proportion of patients who were succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“… 109 Of note, the use of NOACs also lead to faster cardioversion compared to warfarin use when pursuing a standard care approach. 87 , 95 , 100 , 107 , 110 Finally, a meta-analysis of the warfarin vs. NOAC cardioversion trials found a lower stroke rate in patients randomized to NOAC therapy. 111 …”
Section: Studies Comparing Cardioversion On Non-vitamin K Oral Anticomentioning
confidence: 99%
“… 109 Of note, the use of NOACs also lead to faster cardioversion compared to warfarin use when pursuing a standard care approach. 87 , 95 , 100 , 107 , 110 Finally, a meta-analysis of the warfarin vs. NOAC cardioversion trials found a lower stroke rate in patients randomized to NOAC therapy. 111 …”
Section: Studies Comparing Cardioversion On Non-vitamin K Oral Anticomentioning
confidence: 99%